Nilotinib-Induced Elephantine Psoriasis In a Patient With Chronic Myeloid Leukemia: A Rare Case Report and Literature Review - Seyedeh Fatemeh Sadatmadani; Zahra Malakoutikhah; Fatemeh Mohaghegh; Mohammadsaleh Peikar; Mahdi Saboktakin (Elsevier, 2022)
ABSTRACT: Tyrosine kinase inhibitors are anticancer drugs that disrupt signal transduction pathways in protein kinases by different mechanisms. This group of pharmacologic agents has significantly improved the outcome of patients with chronic myeloid leukemia. However, their effect is not limited to cancer cells, and various complications, particularly cutaneous reactions, have been reported. We report a very rare case of a 35-year-old female with a history of chronic myeloid leukemia who presented with elephantine psoriasis after the treatment with nilotinib.Conclusions: This case highlights a critical side effect of tyrosine kinase inhibitors. Awareness of this subject can be useful for better management of similar patients.